Penerapan System Good Corporate Governance, Konservatisme Akuntansi Dan Kinerja Perusahaan - Horas, Erwin; Tamsil, Tamsil; Iqbal, Iqbal (Jurnal Unicorn ADPERTISI, 2023)
The Problem Banking crisis in Indonesia that began late 1997 is not solely caused by the economic crisis, but also caused by not yet implementedgood corporate governance and ethics that based on it. This research was conducted at the banking company listed in Indonesia StockExchange with the aim to test the effect of good corporate governance mechanism on accounting conservatism and company performance. The sample consist of 5  banking companies during the period 2009–2012. Secondary data were tested using multiple regression andpath analysis. The results show that good corporate governance mechanisms have no significant influence on accounting conservatism, has a significant influence on company performance. Nothing found indirect effect of good corporate governance mechanism through accounting conservatism on company performance.